KUALITAS BIODIESEL DARI MINYAK JELANTAH BERDASARKAN PROSES SAPONIFIKASI DAN TANPA SAPONIFIKASI - Edwin Permana; M Naswir (Jurnal Teknologi Terapan, 2020)
Biodiesel is an alternative fuel that can be renewed and as a promising of diesel fuel in the future.  In this study, the production of biodiesel from used waste vegetable oil through the initial treatment reaction saponification and without saponification. The process of producing of biodiesel can used by the transesterification method. The yield of biodiesel were obtained then analysis for quantity by calculating of the percent yield on each yield for biodiesel with saponification successively is 61.68%. The biodiesel product without saponification successively is 81.93%. The quality test produced for biodiesel density test with and without saponification is 0.8871 g / mL and 0.8975 g / mL ,% FFA 0.3375 mg KOH / g and 0.6325 mg KOH / g, and flash point 184 ℃ and 182.6 ℃.